To the theory of welding current impulses optimal for force action - Кrivtsun, I.V.; Demchenko, V.F.; Nоmirovskii, D.А. (Reports of the National Academy of Sciences of Ukraine, 2018)
The problem of the optimum shape of current pulses providing the maximum force action of the electromagnetic field of an arc on a weld pool metal at the welding by a nonmelting electrode with high-frequency modulation of the current has been considered. Necessary and sufficient conditions for getting the optimum shape of welding pulses are given. One of the possible optimum forms of current pulse modulation is a meander. In electric circuits with arc, it is impossible to form rectangular current pulses. Therefore, trapezoidal pulses are considered. The results of parametric optimization of the time parameters of the current pulse modulation are given for such pulses with fixed durations of the leading and trailing fronts.